Chromatin association of the SMC5/6 complex is dependent on binding of its NSE3 subunit to DNA - Zabrady, Katerina; Adamus, Marek; Vondrova, Lucie; Liao, Chunyan; Skoupilova, Hana; Novakova, Marketa; Jurcisinova, Lenka; Alt, Aaron; Oliver, Antony W; Lehmann, Alan R; Palecek, Jan J (Nucleic acids research, 2016)
SMC5/6 is a highly conserved protein complex related to cohesin and condensin, which are the key components of higher-order chromatin structures. The SMC5/6 complex is essential for proliferation in yeast and is involved in replication fork stability and processing. However, the precise mechanism of action of SMC5/6 is not known. Here we present evidence that the NSE1/NSE3/NSE4 sub-complex of SMC5/6 binds to double-stranded DNA without any preference for DNA-replication/recombination intermediates. Mutations of key basic residues within the NSE1/NSE3/NSE4 DNA-binding surface reduce binding to DNA in vitro. Their introduction into the Schizosaccharomyces pombe genome results in cell death or hypersensitivity to DNA damaging agents. Chromatin immunoprecipitation analysis of the hypomorphic nse3 DNA-binding mutant shows a reduced association of fission yeast SMC5/6 with chromatin. Based on our results, we propose a model for loading of the SMC5/6 complex onto the chromatin.
Keywords: Sequence Homology, Amino Acid; Protein Binding; proteiny buněčného cyklu; Cell Cycle Proteins; rekombinace genetická; lidé; Molecular Sequence Data; sekvence aminokyselin; Humans; Schizosaccharomyces pombe - proteiny; Schizosaccharomyces; replikace DNA; DNA Replication; jaderné proteiny; sekvenční homologie aminokyselin; vazba proteinů; DNA; Chromatin; Recombination, Genetic; Nuclear Proteins; Amino Acid Sequence; Schizosaccharomyces pombe Proteins; chromatin; molekulární sekvence - údaje